“Our Lives are Lived in Freestyle”: Social and Dynamic Productions of Breaking and Hip Hop Culture - Marie, Lucas (Curtin University, 2018)
Based on fieldwork with breakers (hip hop dancers) living in New York, Osaka, and Perth, as well from prior experiences within my field of study, this thesis explores how breakers work to produce, sustain and transform hip hop culture. This study emphasises the dynamic, local and unique ways in which hip hop is actively produced and reproduced over time and space, contributing to anthropological writings on culture, process, agency and social action.